2013
DOI: 10.1007/s40291-013-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Proposed Warfarin Dosing Algorithm Based on the Genetic Make-Up of Egyptian Patients

Abstract: VKORC1 (1173C>T) contributes to the warfarin dose variability. Patients' age and genetic variants of VKORC1 account for nearly 20.5% of the variability in warfarin dose required to achieve an INR of 2-3. The success of a prediction equation based on these variables was proved in a different cohort: the predicted dose correlated significantly with the maintenance dose and the equation was more successful among patients with a dose≥35 mg/week. The results of the warfarin algorithm we developed were comparable wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…This is probably due to the sample size, and to the absence of CYP2C9 low-activity genotypes (i.e., *2/*2, *3/*3 and *2/*3). Accordingly, previous studies with similar sample sizes failed to replicate the CYP2C9 effect on a warfarin dose [39]. Nevertheless, since the VKORC1 genotype has a greater effect on the warfarin dose than those reported for CYP2C9 (30 vs 10%), and the VKORC1 minor allele frequency is high in the Turkish population, we replicated the VKORC1 finding in our controlled patients (R 2 = 29.12%).…”
Section: Discussionsupporting
confidence: 83%
“…This is probably due to the sample size, and to the absence of CYP2C9 low-activity genotypes (i.e., *2/*2, *3/*3 and *2/*3). Accordingly, previous studies with similar sample sizes failed to replicate the CYP2C9 effect on a warfarin dose [39]. Nevertheless, since the VKORC1 genotype has a greater effect on the warfarin dose than those reported for CYP2C9 (30 vs 10%), and the VKORC1 minor allele frequency is high in the Turkish population, we replicated the VKORC1 finding in our controlled patients (R 2 = 29.12%).…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with our data, Ekladious et al [14] developed a similar model in a cohort of Egyptian patients including the variables -age, gender, CYP2C9, and VKORC1 SNP genotypes. Regression analysis revealed that age and VKORC1 contributed independently to the overall variability in warfarin dose.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, data from previous reports addressing the value of pharmacogenetic testing in warfarin management in Egyptian patients were infrequent, controversial, and included different polymorphisms [13,14]. The aim of this study was to demonstrate the validity of pharmacogenetic dosing algorithms in Egyptian patients on warfarin therapy.…”
Section: Introductionmentioning
confidence: 98%
“…The use of algorithms based on pharmacogenetics for individualization of dose regimen for warfarin is described by several authors, [22][23][24][25] since genotype is the main determinant of the required warfarin dose and the risk of bleeding, especially in the early months of therapy. 26 Clinical studies have shown that the use of genotype to determine warfarin dose generates variability of results, especially because of the complexity of interrelations between genetic and non-genetic factors.…”
Section: Algorithms Evaluationmentioning
confidence: 99%